Intraoperative Gutter Leaks That Merit Our Attention. (November 2017) - Tanious, Adam; Wooster, Mathew; Giarelli, Marcelo; Armstrong, Paul A.; Back, Martin R.; Shames, Murray L.
Introduction: The natural history and potential morbidity of gutter endoleaks are unclear. We present our experience with intraoperative gutter endoleaks and strategies to determine which of these require intervention. Methods: This is a retrospective review of all patients treated with parallel stent grafts from January 2010 to September 2015. We reviewed all operative records and intraoperative angiograms as well as all postoperative imaging and secondary interventions. All gutter leaks were classified as low-flow/nonsac-enhancing gutter endoleaks or high-flow/sac-enhancing gutter endoleaks. Adjunctive interventions to manage the gutter leaks were noted, as were all subsequent interventions for gutter leak and endoleak management. Results: Seventy-eight patients had 144 parallel stents placed over a 5-year period with an average of 1.8 stents per patient. Twenty-eight patients (36%) had gutter endoleaks diagnosed intraoperatively. Seventeen patients had adjunctive procedures to reduce gutter leaks prior to leaving the operating room (OR). Patients selected for treatment had gutters filling early during completion angiography and/or contrast enhancement of the aneurysm sac. Twenty-two patients (28%) left the OR with low-flow/delayed/nonsac-enhancing gutter endoleaks. At 30 days, a total of 6 persistent gutter endoleaks were diagnosed on computed tomographic angiography. This gives a 73% rate of resolution for low-flow/nonaneurysm sac-enhancing endoleaks. There were 2 de novo endoleaks not detected at the index procedure diagnosed at 6-month follow-up. Of the 8 total postoperative endoleaks, 5 required additional intervention with a 100% success rate. Multivariate analysis revealed that the only significant predictor of having a postoperative endoleak is leaving the OR with an endoleak. Conclusions: Intraoperative treatment of gutter endoleaks has an acceptable rate of resolution. It does have a high rate of converting high-flow endoleaks to low-flow endoleaks. Low-flow/nonsac-enhancing gutter endoleaks have a high rate of spontaneous resolution. Intraoperative gutter endoleaks are not predictive of future aneurysm sac growth.